Heart valve gel coating as well as preparation method and application thereof

By applying a gel coating containing inorganic salts, solvents, alkalis, gel-forming components, coagulation components and anti-inflammatory components on the heart valve, it is solved that the biological heart valve is prone to coagulation after glutaraldehyde crosslinking is possible. , inflammation and calcification problems achieve anticoagulation and anti-inflammatory effects, improving the persistence of the valve and reducing the risk of thrombosis.

CN119405894APending Publication Date: 2025-02-11SUZHOU MUNICIPAL HOSPITAL
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411530091.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Existing biological heart valves are prone to coagulation, inflammation and calcification after glutaraldehyde cross-linking, and have a high risk of thrombosis, making it difficult to achieve both anticoagulation and anti-inflammatory effects.

Method used

Using a heart valve gel coating, the preparation raw materials include inorganic salts, solvents, alkalis, gel-forming components, coagulation components and anti-inflammatory components, which are mixed, dialyzed, lyophilized and Adjust pH to form a gel coating with anticoagulation and anti-inflammatory effects.

Benefits of technology

The anticoagulant and anti-inflammatory effects of the heart valve are achieved, the risk of thrombosis is reduced, the adhesion between the valve and the tissues at the implantation site is improved, the durability of the valve is extended and its mechanical properties are maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to the field of biomedical materials, in particular to the field of A61L27 / 28, and more particularly relates to a heart valve gel coating as well as a preparation method and application thereof. The heart valve gel coating is prepared from the following raw materials: inorganic salt, a solvent, alkali, a gelling component, a blood coagulation component and an anti-inflammatory component, wherein the gelling component comprises silk, the blood coagulation component comprises heparin sodium, and the anti-inflammatory component comprises dopamine hydrochloride. The heart valve gel coating provided by the invention can simultaneously realize anticoagulant and anti-inflammatory effects, and anticoagulant and anti-inflammatory effects are sequentially carried out, so that the pathological requirements of lesions are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biomedical materials, in particular to the field of A61L27 / 28, and more specifically to a heart valve gel coating and a preparation method and application thereof. Background Art

[0002] Clinically, biological heart valves usually need to be cross-linked with glutaraldehyde, which is prone to coagulation, inflammation, and calcification. At the same time, the high risk of thrombosis has always been a problem. The artificial valve implanted in the body is a "foreign body" to the heart. The blood is prone to coagulation in and around the artificial valve, forming thrombi and affecting valve function. If these thrombi fall off, they can cause vascular embolism. Therefore, anticoagulation is required for 6 months after biological valve replacement, and oral warfarin is generally used for anticoagulation treatment. Coagulation reactions also affect the process of endothelialization, aggravate inflammatory reactions, and induce thrombosis. Therefore, inhibiting coagulation and local anti-inflammation are the key to the performance of cardiovascular implant materials.

[0003] The prior art CN112220970B discloses an anticoagulant artificial heart valve material and its preparation method and application. By constructing a fluoride super-lubricating anticoagulant coating on the surface of the biological heart valve material, it can significantly reduce platelet adhesion and whole blood adhesion, greatly improve the anticoagulant performance of the material, but does not achieve local anti-inflammatory effects. Summary of the invention

[0004] In order to solve the above technical problems, the first aspect of the present invention provides a heart valve gel coating, the preparation raw materials of which include: inorganic salts, solvents, alkalis, gel-forming components, coagulation components, and anti-inflammatory components.

[0005] Preferably, the inorganic salt includes sodium carbonate monohydrate and calcium chloride dihydrate.

[0006] Preferably, the solvent includes one or more of ethanol, anhydrous ethanol, isopropanol, and anhydrous isopropanol.

[0007] Further preferably, the solvent includes anhydrous ethanol.

[0008] Preferably, the alkali includes one of sodium hydroxide, potassium hydroxide, ammonia water and calcium hydroxide.

[0009] Further preferably, the alkali comprises sodium hydroxide.

[0010] Preferably, the gelling component includes: one or more of polylactic acid, polyacrylamide, silk, hydroxyethyl cellulose, gelatin, and polyethylene glycol.

[0011] Further preferably, the gel-forming component includes silk.

[0012] Preferably, the coagulation components include: one or more of heparin, heparin calcium, heparin sodium, sodium citrate, and warfarin.

[0013] Further preferably, the coagulation component includes heparin sodium.

[0014] Preferably, the anti-inflammatory component includes: one or more of erythromycin, cephalosporin, azithromycin, roxithromycin, dopamine hydrochloride, amoxicillin, piperacillin, acetaminophen, and metronidazole.

[0015] Further preferably, the anti-inflammatory component includes dopamine hydrochloride.

[0016] A second aspect of the present invention provides a method for preparing a heart valve gel coating, comprising the following steps:

[0017] S1, dissolving the gel-forming components, boiling and washing;

[0018] S2, dialysis purification using dialysis bags and freeze-drying;

[0019] S3, adding coagulation components;

[0020] S4. Add anti-inflammatory components and adjust the pH of the system.

[0021] Further preferably, the method for preparing the heart valve gel coating comprises the following steps:

[0022] S1. On a clean laboratory bench, peel the silk into small pieces, cut into small pieces, prepare a sodium carbonate solution with a mass concentration of 0.5wt%, put the small pieces of silk into the sodium carbonate solution, boil and time for 30 minutes; stir the obtained silk into a ball with a clean glass rod, press to remove water, add deionized water and rinse repeatedly for 3 times until the water is clear after washing; repeat the above boiling-washing steps 2 times, drain the silk degummed 3 times as much as possible, put it on a clean glass culture dish, and then put it in an 80°C oven to dry for 3 hours, and obtain crude silk fibroin after drying;

[0023] S2. Prepare a mixture of calcium chloride dihydrate: ethanol: water = 1:2:8 in molar mass ratio, dissolve the crude silk fibroin, put it in an 80°C water bath and stir for 2 hours, then naturally cool it to room temperature, transfer it to a 14000Da dialysis bag, and dialyze it with deionized water for 72 hours. Cover the dialysis bag with water and change the water every 4 hours. After the dialysis is completed, the liquid in the dialysis bag is divided into 50mL centrifuge tubes, marked, and placed in freeze-drying bottles for freeze-drying. After the freeze-drying is completed, the refined silk fibroin is obtained;

[0024] S3, the freeze-dried refined silk fibroin solid is dissolved in ultrapure water to form a 10wt% silk fibroin solution, and heparin sodium solid is added under stirring until the heparin sodium solid is dissolved;

[0025] S4. Add dopamine hydrochloride solid, and then immediately adjust the pH value of the solution to 8.5 with NaOH solution. Stir and react for 2 hours in an open environment away from light. Seal the solution after the reaction and place it in a constant temperature shaker at 37°C and 300 rpm. React for 3 days to form a gel.

[0026] A third aspect of the present invention provides an application of a heart valve gel coating, which is applied in the field of artificial heart valve preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of gel variable exploration.

[0028] Figure 2 The SEM test images of Example 1 and Comparative Example 1 are shown.

[0029] Figure 3 Schematic diagram of the gelation process.

[0030] Figure 4 These are infrared test images of Example 1 and Comparative Example 1.

[0031] Figure 5 is a schematic diagram of rheological dynamics, where Figure 5 A is the evolution of the storage modulus (G') and loss modulus (G") of the gels in Example 1 and Comparative Example 1, Figure 5 B is a schematic diagram of gel viscosity and shear rate of Example 1 and Comparative Example 1; Figure 5 C is a schematic diagram of Example 1 coated on a heart stent; Figure 5 D is the stability test of Example 1 after coating on the heart stent.

[0032] Figure 6 Schematic diagram of gel degradation of Example 1 and Comparative Example 1; 6A is a schematic diagram of gel appearance, and 6B is a schematic diagram of gel degradation data.

[0033] Figure 7 These are the swelling rate test diagrams of Example 1 and Comparative Example 1.

[0034] Beneficial Effects

[0035] (1) The present invention proposes to coat the valve with a drug-loaded silk fibroin-heparin-based gel. The properties of the gel are regulated to have good shear thinning ability. The gel can be extruded through a syringe and coated on the outer wall of the artificial valve (the thickness is adjustable). After gelation, it adheres to and is fixed to the outer wall of the valve. It can be implanted in the body together with the valve, thereby improving the adhesion between the valve and the tissue of the implantation site, improving the durability of the valve, and maintaining its mechanical properties.

[0036] (2) The gel system is selected as a protein-based gel, the main structure of which is silk fibroin. At the same time, sodium heparin is added in a certain proportion, which also becomes one of the gel structures and can play an anticoagulant role.

[0037] (3) The gel can be loaded with therapeutic drugs for sustained release and anti-inflammatory effects; dopamine hydrochloride can also be added to the gel structure to assist in the anti-inflammatory effect.

[0038] (4) The heart valve gel coating provided by the present invention is relatively novel in design, and can achieve both anticoagulation and anti-inflammation at the same time, and the order is anticoagulation first and then anti-inflammation, which meets the pathological requirements of the lesions.

[0039] (5) The gel system currently achieves gradual degradation within 15 days, with approximately 10% remaining on the 15th day, thus meeting the anticoagulation and anti-inflammatory needs in the "acute phase" after implantation. DETAILED DESCRIPTION

[0040] Example 1

[0041] In the first aspect of this example, a heart valve gel coating is provided, and the raw materials for its preparation are shown in Table 1:

[0042] Table 1

[0043]

[0044]

[0045] The second aspect of this example provides a method for preparing a heart valve gel coating, which specifically comprises the following steps:

[0046] S1. On a clean laboratory bench, peel 20g of silk into small pieces, cut into small pieces, dissolve 5.85g of sodium carbonate monohydrate in 1L of deionized water, prepare a sodium carbonate solution with a mass concentration of 0.5wt%, put the small pieces of silk into the sodium carbonate solution, boil and time for 30 minutes; stir into a ball with a clean glass rod, press to remove water, add deionized water and rinse repeatedly for 3 times until the water is clear after washing; repeat the above boiling-washing steps 2 times, drain the silk degummed 3 times as much as possible, put it on a clean glass culture dish, and then put it in an 80°C oven to dry for 3 hours, and obtain crude silk fibroin after drying;

[0047] S2. Prepare a mixture of calcium chloride dihydrate: ethanol: water = 1:2:8 (calcium chloride hydrate is weighed in powder form, because the amount is large and the block is difficult to dissolve; after weighing, place it in an ice bath for ultrasonic dissolution, because the dissolution process generates a lot of heat, and the solute may volatilize without an ice bath), add crude silk fibroin, dissolve it in a mass ratio of mixed solution: crude silk fibroin = 20:1, put it in an 80°C water bath and stir for 2 hours, then naturally cool it to room temperature, transfer it to a 14000Da dialysis bag, boil the dialysis bag in boiling water for 10 minutes in advance, disinfect and sterilize the dialysis clamps in advance, and the dialysis bag should not be filled with too much mixed solution, and 1 / 3 of the space should be left, dialyze with deionized water for 72 hours, cover the dialysis bag with water, and change the water every 4 hours. After the dialysis is completed, the liquid in the dialysis bag is divided into 50mL centrifuge tubes, marked, and placed in freeze-drying bottles for freeze-drying. After freeze-drying, refined silk fibroin is obtained;

[0048] S3, dissolving the freeze-dried refined silk fibroin with ultrapure water to form a silk fibroin (SF) solution with a mass concentration of 10 wt%, adding 2 mg of solid heparin sodium (Hep) to 2 mL of the 10 wt% silk fibroin (SF) solution under stirring, and waiting for the solid heparin sodium to dissolve;

[0049] S4. Add dopamine hydrochloride (DA) solid, and then immediately adjust the pH of the solution to 8.5 with 0.1M NaOH solution. Stir for 2 hours in an open environment away from light. Seal the solution after the reaction and place it in a constant temperature shaker at 37°C and 300 rpm. React for 3 days to form a gel, which is recorded as SF@Hep@PDA@Gel, where PDA is polydopamine hydrochloride.

[0050] A third aspect of the present invention provides an application of a heart valve gel coating, which is applied in the field of artificial heart valve preparation.

[0051] Comparative Example 1

[0052] This example provides a method for preparing a heart valve gel coating, which specifically comprises the following steps:

[0053] S1. On a clean laboratory bench, peel 20g of silk into small pieces, cut into small pieces, dissolve 5.85g of sodium carbonate monohydrate in 1L of deionized water, prepare a sodium carbonate solution with a mass concentration of 0.5wt%, put the small pieces of silk into the sodium carbonate solution, boil and time for 30 minutes; stir into a ball with a clean glass rod, press to remove water, add deionized water and rinse repeatedly for 3 times until the water is clear after washing; repeat the above boiling-washing steps 2 times, drain the silk degummed 3 times as much as possible, put it on a clean glass culture dish, and then put it in an 80°C oven to dry for 3 hours, and obtain crude silk fibroin after drying;

[0054] S2. Prepare a mixture of calcium chloride dihydrate: ethanol: water = 1:2:8 (calcium chloride is weighed in powder form, because the amount is large and the block is difficult to dissolve; after weighing, place it in an ice bath for ultrasonic dissolution, because the dissolution process generates a lot of heat, and the solute may volatilize without an ice bath), add crude silk fibroin, and dissolve it in a mass ratio of mixed solution: crude silk fibroin = 20:1, put it in an 80°C water bath and stir for 2 hours, then naturally cool it to room temperature, and transfer it to a 14000Da dialysis bag. The dialysis bag is boiled in boiling water for 10 minutes in advance, and the clamps for dialysis are disinfected and sterilized in advance. The dialysis bag should not be filled with too much mixed solution, and 1 / 3 of the space should be left. Use deionized water for 72 hours, cover the dialysis bag with water, and change the water every 4 hours. After the dialysis is completed, the liquid in the dialysis bag is divided into 50mL centrifuge tubes, marked, and placed in freeze-drying bottles for freeze-drying. After the freeze-drying is completed, the refined silk fibroin is obtained;

[0055] S3. The freeze-dried refined silk fibroin was dissolved in ultrapure water to form a 10wt% silk fibroin (SF) solution. Under stirring, 2mL of 10wt% silk fibroin (SF) solution was added with 2mg of solid heparin sodium (Hep). After the solid heparin sodium was dissolved, it was placed in a constant temperature shaker at 37°C and 300rpm. The solution was reacted overnight to form a gel, which was recorded as SF@Hep@Gel.

[0056] Performance Testing

[0057] 1. Study on the properties of gelling

[0058] The effect of different masses of heparin sodium on gelling properties was investigated: 0 mg, 2 mg, and 5 mg of Hep were added during the preparation of Comparative Example 1, and the appearance of the gel was observed;

[0059] The effect of different masses of dopamine hydrochloride on the gel-forming properties was investigated: during the preparation process of Example 1, 0 mg, 0.5 mg, 1 mg, 2 mg, 5 mg, and 10 mg of Hep were added respectively, and the appearance of the gel was observed.

[0060] The test results are detailed in Figure 1 .

[0061] When the concentration and volume of SF were fixed and the content of Hep was adjusted, when the Hep content was 2 mg, the solution could be transformed into a gel, and when the Hep content was further increased to 5 mg, there was no significant change in the solution. When the concentration and volume of SF and the content of Hep were further fixed, the content of DA was adjusted.

[0062] The results showed that as the DA content increased, the solution gradually changed from a solution state to a gel state. And at the same time, as the DA content increased, the color of the gel gradually changed from brown to black.

[0063] 2. SEM characterization

[0064] The freshly prepared gel samples of Example 1 and Comparative Example 1 were cut into 1×1×1 cm 3 Add 10 mL of distilled water to the square gel block and place it in a 4°C refrigerator overnight. After swelling equilibrium, put the sample into liquid nitrogen for quick freezing for 30 min, and then immediately put it into a freeze dryer for drying for 24 h. Glue the block gel sample directly onto the conductive glue.

[0065] An Oxford Quorum SC7620 sputtering coater was used to spray gold for 45 seconds at a current of 10 mA. A TESCANMIRA LMS scanning electron microscope was then used to photograph the sample morphology for testing. The accelerating voltage during morphology photography was 3 kV.

[0066] The test results are as follows Figure 2 shown.

[0067] The results showed that the gel presented a mutually cross-linked three-dimensional network structure, and compared with SF@Hep@Gel gel, the pores of the SF@Hep@PDA@Gel gel group were more uniform and the pore size was significantly reduced.

[0068] 3. Demonstration of gelation process

[0069] Observe the gelation process demonstration diagrams of Example 1 and Comparative Example 1.

[0070] The experimental results are as follows Figure 3 shown.

[0071] After SF and Hep were mixed, the solution was uniformly opaque milky white. After being incubated at 37°C overnight, the solution turned into a milky white opaque gel. DA powder was added, and after the DA powder was completely dissolved, the pH of the mixed solution was adjusted to 8.5 with 0.1M NaOH solution, and then oxidized for half an hour under light-proof conditions. The solution gradually changed from opaque milky white to uniform brown, indicating that DA was successfully oxidized to PDA (polydopamine hydrochloride). Further, after being incubated in a 37°C constant temperature shaker for 3 days, the mixed solution gradually turned into a gel.

[0072] 4. Determination of porosity

[0073] First, weigh the mass m1 of the dried gel sample and measure the volume V = S × h = πr 2 ×h), then completely immerse it in anhydrous ethanol and draw negative pressure, keep it for 30 minutes, then take it out and weigh it m2. The porosity calculation formula is R = (m2-m1) / ρv, where R is the porosity and ρ is the density of anhydrous ethanol (ρ = 0.79g / cm 3 ), the test results are shown in Table 2.

[0074] Table 2

[0075] Porosity (R) <![CDATA[Volume (πr 2 ×h)]]> <![CDATA[Mass difference (m2 - m1)]]> Comparative Example 1 0.1082 <![CDATA[9.0746cm 3 ]]> (9.4478-8.6722)g Example 1 0.1718 <![CDATA[9.0746cm 3 ]]> (8.5254-7.2951)g

[0076] The results show that the porosity of SF@Hep@Gel and SF@Hep@PDA@Gel is 0.1082 and 0.1718 respectively. Compared with SF@Hep@Gel, the porosity of SF@Hep@PDA@Gel is significantly increased, which is consistent with the SEM results.

[0077] 5. Fourier transform infrared spectroscopy

[0078] Take 20 mg of dry gel sample and place it between two glass slides to form a sheet. In a dry environment, place the ATR accessory in the optical path of the spectrometer, scan the air background, and then place the block / film sample surface close to the crystal surface of the ATR accessory, and then collect the infrared spectrum of the sample with a resolution of 4 cm -1 , the scanning times are 32 times, and the test wave number range is 500-4000cm -1 .

[0079] The test results are detailed in Figure 4 .

[0080] The analysis results show that SF is at 1646.4cm -1 (Amide I) and 1522.0 cm -1 The absorption peaks of SF@Hep@Gel gel at 1612.1cm 1 and 1512.0cm 1 (amide I and amide II) can be attributed to the β-folding conformation of silk fibroin. This indicates that hydrogen bonds are successfully formed between silk fibroin and heparin, thereby inducing the transformation of silk fibroin from random coil to β-folding conformation. DA at 3333.6cm -1 、3032.1cm -1 、2947.1cm -1 and 1502.4cm -1 The absorption peaks at 3500-3000cm correspond to the stretching vibration of eNH in DA, eOH in the catechol group, and the stretching vibration of aromatic eCH and CC in the benzene ring, which are the characteristic peaks of DA. After DA is polymerized into polydopamine hydrochloride (PDA), the absorption peaks at 3500-3000cm -1 The peak at 1110.39cm is mainly derived from the stretching vibration of free -NH2 in poly-dopamine hydrochloride. The intensity of each characteristic peak of DA weakened after polymerization. In addition, compared with SF@Hep@Gel, the peak at 1110.39cm in SF@Hep@PDA@Gel was -1 and 813.51cm -1The new peaks at 1624.0cm and 1624.0cm respectively are attributed to the stretching of CeO in phenol and the bending of eOH in the plane of poly(dopamine hydrochloride). The above results indicate that poly(dopamine hydrochloride) can be successfully coupled to the silk protein chain. However, SF@Hep@PDA@Gel (1624.0cm -1 and 1511.0cm -1 ), the degree of gel transfer of SF@Hep@Gel was lower than that of DA@Hep@Gel, which may be due to the formation of Schiff base bonds between DA and SF during the formation of PDA.

[0081] 6. Rheological dynamics

[0082] The ungelled gel solution was placed in a mold to prepare a gel sample with a diameter of 20 mm and a height of 2 mm. The rheological properties of the gel were characterized using a Mars60 rheometer, and an oscillation rate sweep test was performed at 25±0.2°C, with γ=0.1-1000% and f=1 Hz. The temperature and strain (γ=1%) were fixed, and only the frequency (0.1-100 Hz) was changed to obtain the shear rate-viscosity relationship curve.

[0083] The test results of rheological dynamics of Example 1 and Comparative Example are as follows: Figure 5 shown; Figure 5 A is the evolution of the storage modulus (G') and loss modulus (G") of the gels in Example 1 and Comparative Example 1, Figure 5 B is a schematic diagram of gel viscosity and shear rate of Example 1 and Comparative Example 1; Figure 5 C is a schematic diagram of Example 1 coated on a heart stent; Figure 5 D is the stability test of Example 1 after coating on the heart stent.

[0084] The main purpose of rheological dynamics is to study the time-dependent flow and deformation of materials under external conditions. The instrument that measures rheological properties is called a rheometer. The parameters generally tested for gels include elastic modulus (G') and viscous modulus (G"). The elastic modulus characterizes the solid-like behavior of the material, while the viscous modulus refers to the heat dissipation generated by the deformation of the material when the deformation stops after the applied force is removed, which characterizes the liquid-like behavior of the material, so it is also called the loss modulus.

[0085] When the storage modulus G' is much larger than the loss modulus G", the material mainly undergoes elastic deformation, so the material is solid; when the loss modulus is much larger than the storage modulus, the material mainly undergoes viscous deformation, so the material is liquid; when the storage modulus and loss modulus are equal, the material is semi-solid. Gel is a typical semi-solid material that has both solid and liquid properties. Figure 5As shown in A, when the strain range is 0.1 - 1%, the G' of the gel is distributed between 60000 - 70000 Pa. The material mainly undergoes elastic deformation and the gel structure is well maintained. While the G" is distributed between 5000 - 10000 Pa, and G' is greater than G". When the strain range is greater than 1%, an intersection appears between G' and G". At this time, the sample is at the gel - sol transition point, that is, the state of the sample begins to change. When G' < G", the material mainly undergoes viscous deformation, indicating that the sample mainly exhibits liquid characteristics, meaning that the gel structure collapses at this time. Meanwhile, with the addition of PDA, the G' of the gel slightly increases, possibly because the hydroxyl group of PDA and the amino group of SF increase the number of hydrogen bonds and Schiff base reaction sites.

[0086] Then, fix the shear strain and observe the changes in viscosity and shear rate. The results are as Figure 5 shown in B. The viscosity of the prepared gel decreases with the increase of stress, that is, the shear - thinning effect appears. All the above results indicate that the gel has injectability, and its injection demonstration is as Figure 5 shown on the right side of B. Further verify the coating of the gel on the heart valve coating and its stability. The results are as Figure 5 shown in C and 5D. The gel can be evenly coated on the mold made of heart valve material by injection and smearing methods. And by uniformly moving up and down in the PBS solution, observe the adhesion of the gel to the stent material. The results show that only a small amount of the gel falls off after 3 minutes in the PBS solution, indicating that the adhesion between the gel and the stent is good and has a certain stability.

[0087] 7. Gel degradation analysis

[0088] Add phosphate - buffered saline (PBS) to the gel sample of constant weight, place it in an incubator at 37°C for soaking, test the change in the weight of the gel sample after soaking for different times, calculate the percentage of weight loss relative to the original gel sample weight, and define it as the degradation rate of the gel.

[0089] Degradation rate (%) = (W0 - W t ) / W0 × 100% (W0 is the initial weight of the gel, W t is the weight of the gel measured at different soaking times)

[0090] The degradation test results are as Figure 6 shown in A and 6B;

[0091] Figure 6 are the gel degradation schematic diagrams of Example 1 and Comparative Example 1; among them, 6A is the schematic diagram of the gel appearance, and 6B is the schematic diagram of the gel degradation data.

[0092] The in vitro degradation performance of the gel is also an important performance parameter because it affects the mechanical properties of the gel. In this chapter, the degradation performance of the gel was studied in vitro using the hydrolysis method. Figure 6 As shown in A and 6B, as time goes by, the gel sample gradually disintegrates from the original regular gel block to the gel fragment. And the supernatant gradually becomes turbid. At the same time, the quantitative results are as follows Figure 5 B shows that at 1D, the mass of the gel increased significantly, which may be due to the swelling of the gel due to water absorption. Then, with the increase of time, the mass of the gel gradually decreased, and at 21D, the remaining masses of SF@Hep@Gel and SF@Hep@PDA@Gel were 21.5% and 15.5%, respectively.

[0093] 8. Swelling rate test

[0094] First, freeze-dry the prepared gel, and then assign the mass of the freeze-dried gel to W0. Subsequently, soak the freeze-dried gel in PBS (pH = 7.2) for 2 hours. Then filter the sample with filter paper at 10min, 20min, 30min, 60min, 90min, and 120min, and record the gel weight at each time point as Wt. Take 3 parallel samples for each measurement. The calculation formula of the swelling rate (SR) is as follows:

[0095] SR=(W t -W0) / W0×100%

[0096] Test results such as Figure 7 shown.

[0097] Figure 7 The swelling rate of SF@Hep@Gel and SF@Hep@PDA@Gel gels as a function of time (0-120 min) is shown. After soaking in PBS solution for 10 min, all gels showed rapid swelling, with a slight increase in swelling rate from 10 to 30 min and a basic unchanged swelling rate from 30 to 120 min, indicating that the gel was in a swelling equilibrium state. In addition, the swelling rate of SF@Hep@PDA@Gel gel was significantly greater than that of SF@Hep@Gel, which may be due to the fact that the gel of SF@Hep@PDA@Gel gel is denser and has a larger porosity than that of SF@Hep@Gel.

Claims

1. A heart valve gel coating, characterized in that: The raw materials for preparing the heart valve gel coating include: inorganic salt, solvent, alkali, gelling component, blood coagulation component and anti-inflammatory component.

2. The heart valve gel coating according to claim 1, characterized in that: The gelling components include: one or more of polylactic acid, polyacrylamide, silk, hydroxyethyl cellulose, gelatin and polyethylene glycol.

3. The heart valve gel coating according to claim 2, characterized in that: The gel-forming component includes silk.

4. The heart valve gel coating according to claim 3, characterized in that: The coagulation components include: one or more of heparin, heparin calcium, heparin sodium, sodium citrate, and warfarin.

5. The heart valve gel coating according to claim 4, characterized in that: The blood coagulation component includes heparin sodium.

6. The heart valve gel coating according to claim 5, characterized in that: The anti-inflammatory component comprises one or more of erythromycin, cephalosporin, azithromycin, roxithromycin, dopamine hydrochloride, amoxicillin, piperacillin, acetaminophen and metronidazole.

7. The heart valve gel coating according to claim 6, characterized in that: The anti-inflammatory component includes dopamine hydrochloride.

8. The heart valve gel coating according to claim 7, characterized in that: The solvent includes one or more of ethanol, anhydrous ethanol, isopropanol and anhydrous isopropanol.

9. A method for preparing a heart valve gel coating according to claim 8, characterized in that: The preparation method comprises the following steps: S1, dissolving the gel-forming components, boiling and washing; S2, dialysis purification using dialysis bags and freeze-drying; S3, adding coagulation components; S4. Add anti-inflammatory components and adjust the pH of the system.

10. An application of the heart valve gel coating according to claim 8, characterized in that: Applied in the field of preparation of artificial heart valves.

Citation Information

Patent Citations

  • An anticoagulant artificial heart valve material, its preparation method and application

    CN112220970B